2009
DOI: 10.1007/s12036-009-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid neutron capture process in supernovae and chemical element formation

Abstract: The rapid neutron capture process (r-process) is one of the major nucleosynthesis processes responsible for the synthesis of heavy nuclei beyond iron. Isotopes beyond Fe are most exclusively formed in neutron capture processes and more heavier ones are produced by the r-process. Approximately half of the heavy elements with mass number A 70 and all of the actinides in the solar system are believed to have been produced in the r-process. We have studied the r-process in supernovae for the production of heavy el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Recently, it has been shown, on the other hand, that 164 Er, 152 Gd and 180 Ta may have large s-process contributions, nevertheless, and that the ν-process may contribute to 138 La and 180 Ta (see, e.g., [3] and references therein). The remaining p nuclei are thought to be produced in the γ-process which includes combination of (γ,n), (γ,p) and (γ,α) reactions [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown, on the other hand, that 164 Er, 152 Gd and 180 Ta may have large s-process contributions, nevertheless, and that the ν-process may contribute to 138 La and 180 Ta (see, e.g., [3] and references therein). The remaining p nuclei are thought to be produced in the γ-process which includes combination of (γ,n), (γ,p) and (γ,α) reactions [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The Hartree-Fock calculation including forbidden transitions with Skyrme interaction and pairing correlations can also well reproduce measured half-lives of neutron-rich nuclei with A ≈ 190 [30]. In other studies [10,[31][32][33], it was found that the determination of the neutron density and temperature conditions for the (γ, n) − (n, γ) equilibrium establishment or WP approximation strongly depends on neutron and/or two-neutron separation energies of neutron-rich nuclei. In particular, the deviations in two-neutron separation energies of 78 Ni and 84 Zn due to the differences among the RMF [34], FRDM [35], and WS [36,37] mass models lead to a large change, from 10 23 to 10 26 cm −3 at 1 GigaKelvin (GK), in the neutron density required by the N = 50 WP [33].…”
Section: Introductionmentioning
confidence: 60%
“…The produced very neutron rich progenitor nuclei then undergo a series of β − -decays until they reach a stable nucleus whose calculated abundance can then be compared with observation. The r-process path and the elements obtained in these astrophysical conditions are presented in an earlier paper by Baruah et al (2009). It was recognised that the extremely high neutron densities and temperatures needed were probably attainable only in dynamical events, i.e.…”
Section: Introductionmentioning
confidence: 92%